การเตรียมนาโนคอมพอสิตพอลิโพรพิลีน/แป้งมันสำปะหลัง/มอนต์มอริลโลไนต์ - สุรีรัตน์ ใช้เอกปัญญา (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
This research aims to prepare biodegradable nanocomposites of polypropylene (PP)/cassava starch/montmorillonite (MMT). MMT was first modified by sorbitol using a high speed mixer at 3,000 rpm for 2 min. Cassava starch was then mixed with various amounts of modified-MMT (1, 3 and 5 phr), sorbitol and formamide on a two-roll mill to obtain thermoplastic starch (TPS)/modified-MMT nanocomposites. It was found that the nanocomposite of 5 phr modified-MMT exhibited highest tensile strength. X-ray diffractogram and transmission electron micrograph of the TPS/modified-MMT revealed that the nanocomposite formed was exfoliated. Then, PP/EBS wax at weight ratio of 90/10 was mixed with various amounts of the TPS/modified-MMT nanocomposite (10, 20 and 30 parts per hundred of PP/EBS wax) using twin screw extruder followed by compression molding. The obtained PP/TPS/modified-MMT nanocomposites were characterized for their tensile properties, morphology, thermal behaviors, water absorption and biodegradability. The results showed that the tensile properties of the nanocomposites decreased with the higher amount of TPS/modified-MMT nanocomposite. Moreover, blending of TPS and modified-MMT with PP displayed slightly effect on thermal stability, melting point and crystalline temperature of the nanocomposites. However, water absorption and biodegradability of the nanocomposites were enhanced with the increasing amount of TPS.